2021
DOI: 10.2105/ajph.2020.305990
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 Among African Americans: An Action Plan for Mitigating Disparities

Abstract: As the COVID-19 pandemic has unfolded across the United States, troubling disparities in mortality have emerged between different racial groups, particularly African Americans and Whites. Media reports, a growing body of COVID-19-related literature, and long-standing knowledge of structural racism and its myriad effects on the African American community provide important lenses for understanding and addressing these disparities. However, troubling gaps in knowledge remain, as does a need to act. Using the bes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(47 citation statements)
references
References 27 publications
1
45
0
1
Order By: Relevance
“…With respect to race/ethnicity, limited information has been published on its influence on PsA and AS prevalence and treatment, although racial disparities in treatment have been well documented for other diseases, including cardiovascular disease, cancer, and COVID-19 [ 32 34 ]. In previous studies, black patients with PsA or AS were found to have more severe disease than white patients, based on various disease and quality of life measurement criteria, including patient-physician global scores, PSORIasis Index of Quality of Life, and Short Form-36 mental component score for PsA and Bath AS Disease Activity Index, Bath AS Functional Index, Bath AS Radiographic Index, and the modified Stoke AS Spine score for AS [ 19 , 20 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…With respect to race/ethnicity, limited information has been published on its influence on PsA and AS prevalence and treatment, although racial disparities in treatment have been well documented for other diseases, including cardiovascular disease, cancer, and COVID-19 [ 32 34 ]. In previous studies, black patients with PsA or AS were found to have more severe disease than white patients, based on various disease and quality of life measurement criteria, including patient-physician global scores, PSORIasis Index of Quality of Life, and Short Form-36 mental component score for PsA and Bath AS Disease Activity Index, Bath AS Functional Index, Bath AS Radiographic Index, and the modified Stoke AS Spine score for AS [ 19 , 20 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…As a foundation, institutional investment in widely accessible, integrated healthcare delivery will be important to ensure early access to care during future pandemics. Transportation to and from medical appointments, robust language services, and community health worker outreach may be utilized by medical homes to further bridge the gaps in healthcare access and utilization [ 41 ]. Long-term community investments are needed to support the goal of health equity [ 42 ].…”
Section: Covid-19 Disparities In Vaccinationsmentioning
confidence: 99%
“…The need to address trust in order to mitigate the continued impact of COVID-19 especially in minority communities already impacted by health disparities has been recognized in recent literature [ 25 , 26 ]. However, the relationship between institutional mistrust and vaccine hesitancy deserves more attention [ 27 , 28 ], especially in relation to the COVID-19 pandemic.…”
Section: Introductionmentioning
confidence: 99%